TAXATION OF CRYPTOCURRENCY TRANSACTIONS: A COMPARATIVE ANALYSIS OF INTERNATIONAL APPROACHES AND IMPLICATIONS FOR ACCOUNTING AND AUDITING - BONDAR, Mykola; OSTAPIUK, Nataliia; TKALENKO, Svitlana (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article analyzes the taxation of cryptocurrency transactions in the context of developing effective fiscal policy and ensuring transparency in the digital economy. The authors summarize international experience in regulating the tax status of cryptocurrencies and analyze the approaches used in the US, UK, Germany, Japan, and other countries. Examples are given of how cryptocurrencies are classified as property, financial assets, or other categories depending on the legal system, which significantly affects the application of direct and indirect taxes.Particular attention is paid to the analysis of Ukraine's legal framework for the taxation of cryptocurrency transactions. Existing contradictions between legislative acts, including the Law of Ukraine “On Virtual Assets” and the Tax Code of Ukraine, in particular regarding the procedure for declaring income, the tax base, and data sources for control, are identified. The authors emphasize that national legislation needs to be substantially updated to ensure clarity of tax obligations and avoid double interpretation of the rules.The article also examines problematic aspects of accounting and auditing of cryptocurrency transactions in the Ukrainian context. It is emphasized that there are currently no approved methodological guidelines for accounting for digital assets, and the audit of such transactions is complicated by insufficient regulation of procedures for checking, verifying crypto wallets, and determining fair value.The authors offer a number of practical recommendations for improving national tax legislation and harmonizing approaches to accounting and control of cryptocurrency transactions. In particular, they emphasize the need to adopt separate tax rules for digital assets, introduce transparent reporting rules, and define criteria for valuing such assets within the framework of national accounting and auditing standards.
Keywords: cryptocurrency; digital assets; taxation; blockchain; accounting; financial reporting; audit; risk; compliance